The effect of treatment regimens on salivary cortisol levels in patients with chronic musculoskeletal disorders. Issue 1 (January 2020) - Papandreou, Maria; Philippou, Anastassios; Taso, Orjona; Koutsilieris, Michael; Kaperda, Alexandra
Abstract: Background: Increased levels of circulating cortisol have been associated with pain severity in patients with chronic musculoskeletal disorders (CMD). Little is known about the potential association between pain management and salivary cortisol alterations in CPM patients treated with different regimens. Objectives: This prospective feasibility study aimed to determine the effect of two treatment regimens in comparison with sham therapy on pain intensity and disability and salivary cortisol concentration (SCC) in patients with CMD. Methods: Thirty patients were randomly assigned to 3 groups of 10: two experimental groups (A and B) and a control group (C). The experimental groups followed physiotherapy treatment (A) or acupuncture (B), while the control group (C) followed a sham therapy for 10 sessions. Pain data were collected using the Chronic Pain Grade (CPG) questionnaire and SCC was measured by enzyme-linked immunosorbent assay at pre- and posttreatment. Results: Repeated-measures analysis of variance showed that patients treated with acupuncture experienced greater decreases in pain intensity/pain disability ( P < 0.05) than the physiotherapy and sham therapy groups. No statistical differences were found between the three groups for the SCC outcome variable. Bonferroni adjustments showed that the mean values of SCC were significantly decreased at posttreatment ( P < 0.05) across the three groups. Conclusion: There was a significant decrease in both pain and cortisol outcomes at posttreatment in patients with CMD. Because of the limitations of this study, we cannot draw conclusions regarding whether the lower SCC could be an indication of pain reduction in patients with CMD.